2016
DOI: 10.1016/j.chemosphere.2016.08.076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrical stimulation on the fate of sulfamethoxazole and tetracycline with their corresponding resistance genes in three-dimensional biofilm-electrode reactors

Abstract: Three-dimensional biofilm-electrode reactors (3D-BERs), which possess a large effective area to drive the reductive degradation of contaminants, have recently attracted attention for wastewater treatment. There have been few studies of the potential and risks of the application of this system on the removal of antibiotics. Here four 3D-BERs were designed to initially assess the potential for electrical stimulation to remove sulfamethoxazole (SMX), tetracycline (TC) and chemical oxygen demand, and to study the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(16 citation statements)
references
References 33 publications
(48 reference statements)
0
15
0
1
Order By: Relevance
“…10 Oenanthe javanica was planted in the top layer and grew vigorously. The synthetic domestic wastewater containing glucose (0.225 g L -1 ), KH 2 PO 4 (0.004 g L -1 ), NH 4 Cl (0.020 g L -1 ), NaCl (0.15 g L -1 ), and 0.20 mL concentrated trace element solution (Cao et al, 2015;Zhang et al, 2016). The synthetic domestic was fed continuously into the VUF-CWs at the bottom inlet using peristaltic pumps.…”
Section: Configuration and Operation Of Vuf-cwsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Oenanthe javanica was planted in the top layer and grew vigorously. The synthetic domestic wastewater containing glucose (0.225 g L -1 ), KH 2 PO 4 (0.004 g L -1 ), NH 4 Cl (0.020 g L -1 ), NaCl (0.15 g L -1 ), and 0.20 mL concentrated trace element solution (Cao et al, 2015;Zhang et al, 2016). The synthetic domestic was fed continuously into the VUF-CWs at the bottom inlet using peristaltic pumps.…”
Section: Configuration and Operation Of Vuf-cwsmentioning
confidence: 99%
“…Similar with previous studies, the abundance of sulI was higher than that of the sulII and sulIII genes (Ji et al, 2012;Nolvak et al, 2013). The different abundance of sul genes in the CWs were mainly attributed to their specific acquisition mechanisms (McKinney et al, 2010;Zhang et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…revealed the method of degradation of SMX 6.0 mgL -1 in a microbial electrolytic cell within seven days. Another study by Zhang et al [24] observed that the removal rate of 200μgL -1 of sulfamethoxazole (SMX) in a three-dimensional biofilm electrode reactor (3D-BER). The system reached 85.5 ̶ 90% removal with hydraulic retention time (HRT) of 40 h. While the multipurpose treatment of solid-phase mixtures (granular activated carbon), Song et al [25] demonstrated that the removal performance of antibiotics in 3-Dimensional biofilm electrode reactors (3DBER), in solid phase environment and integration possibilities with other technologies, as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…16 The MFC can convert energy and produce electricity while degrading organic matter, 17,18 such as easily degradable 19,20 and bio-refractory organics. 21,22 Several studies have recently focused on the degradation of TCs by MFC 23,24 to improve TC removal. However, the characterization and degradation mechanisms of the different kinds of TCs by MFC remain unknown.…”
Section: Introductionmentioning
confidence: 99%